Mechanisms of induction of the stress-responsive transcription factors HsfA2 and DREB2A by 12-oxo-phytodienoic acid in Arabidopsis thaliana. Issue 4 (3rd April 2014) - Masuda, Shinji; Tokaji, Yoshihito; Kobayashi, Yuichi; Ohta, Hiroyuki
Abstract: OPDA (12-oxo-phytodienoic acid) not only is an intermediate in jasmonic acid biosynthesis but also regulates gene expression, although mechanisms of OPDA-induced signaling are largely unknown. Here, we measured transcriptional responses of the OPDA-responsive genes HsfA2 and DREB2A to the protein synthesis inhibitor cycloheximide and to the HSP90 inhibitor geldanamycin. The results suggest that HSP90 and other proteins suppress the expression.